Evaluación del herbicida enide 50W, en chiltoma para suelos pesados del valle de Estelí - Rodríguez Pérez, Francisco Ramon; López Díaz, Oskar Zacarias (Estelí (Nicaragua), 1987)
Sumario (Es)
Ilus.
Tesis (Tec Agr)
Keywords: SOLANACEAE; MALEZAS; ESCARDA; PLANTAS PERENNES; HERBICIDAS; EVALUACION; SUELO ARCILLOSO; NICARAGUA; ESTELI